2022
DOI: 10.1177/10911421221124561
|View full text |Cite
|
Sign up to set email alerts
|

Ideology, Party, and Opinions of Taxes on the Rich and Middle Class in the United States: Evidence from the 2016 General Social Survey

Abstract: This paper examines attitudes toward taxes on the rich and middle class in the United States with emphasis on the impacts of political ideology and party identification. Using the 2016 General Social Survey, we estimate bivariate ordered probit models for a full cross-sectional sample, and subsamples stratified by party. Results suggest that proposals to reduce income and wealth inequalities and/or fund large federal expenditure increases by raising taxes on the rich will have difficulty in gaining the politic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Republican vote share (-) Political factors may play a role in determining tax rates, and we include Republican vote share as a variable in our model. Previous research has suggested that there may be a correlation between conservative political views and a preference for lower taxes or tax rates (Yen & Zampelli, 2022). Thus, we hypothesize that areas with a higher share of Republican voters may be less likely to adopt or increase an HMT rate.…”
Section: Determinant Model For Hotel/motel Tax Ratementioning
confidence: 88%
“…Republican vote share (-) Political factors may play a role in determining tax rates, and we include Republican vote share as a variable in our model. Previous research has suggested that there may be a correlation between conservative political views and a preference for lower taxes or tax rates (Yen & Zampelli, 2022). Thus, we hypothesize that areas with a higher share of Republican voters may be less likely to adopt or increase an HMT rate.…”
Section: Determinant Model For Hotel/motel Tax Ratementioning
confidence: 88%